Penglipuran Tourist Village, Kubu Village, Bangli Regency, Bali in Maintaining the Sustainability of Cultural Values and Bamboo Forests: A Legal Sociology Perspective - Astara, I Wayan Wesna; Wesna, Putu Ayu Sriasih; Wijaya, I Kadek Merta; Kosasih, Johannes Ibrahim; Sumardika, I Nyoman; Gianyar, I Made; Budiartha, Nyoman Putu (Formosa Journal of Multidisciplinary Research, 2024)
The development of the Penglipuran tourism village based on culture ensures the welfare of the Penglipuran indigenous community. The profit-sharing management pattern with the Bangli Regency government Based on the Cooperation Agreement with the Penglipuran Traditional Village Concerning the Management of Tourism in the Penglipuran Tourism Village Number 415.4/23/PKS/PKKP/2020; Number 01/S.P/X/2020; concerning the Management of the Penglipuran Tourism Village. The Penglipuran traditional village is entitled to a reward of 60% (sixty percent) of the gross levy results. Deposit all levy results (gross) every week/7x24 (seven times twenty-four) hours to the Regional Treasury through the Receiving Treasurer at the Bangli Regency Tourism and Culture Office. This Cooperation Agreement is valid for five (five) years starting from January 1, 2021. No later than 2 (two) months before this cooperation agreement ends, the parties agree to notify each other of their intentions if they wish to extend this cooperation.